Modelling of sintering behaviour of Al-49.6wt%Zn powder compacts (2002)
Al-Zn alloys find commercial use in aircrafts and cars. During multiphase sintering of powders, dimentional changes take place. It is necessary to accurately predict what dimentional changes will occur so that post sintering operatings will take care of this change. The sintering behaviour of Al-49.6wt% Zn powder compacts has been studied. Mathematical models for the effect of pressure and temperature on dimensional changes during sintering were obtained. Sintering temperature was kept constant at 435oC.Powder compact size was also kept constant.It was observed that, at a compacting pressure of 288Mpa there was zero shrinkage after 6 minutes of sintering at 435oC. With compacting pressure less than 288MPa and sintering for 150minutes, there was no single pressure where both diametric and longitudinal shrinkage was zero. It was only possible to keep the longitudinal and diametric shrinkage as low as possible(0.35%) at a compacting pressure of 205MPa. This shows that it is possible to have no shrinkage in the sintering operation of AL-49.6wt%Zn powder compacts which implies that no post sintering operation is neccessary if dimensional accuracies are required.